The Imperial Cities and Imperial Reform in Late Medieval and Early Reformation Germany, 1410–1532 - Hardy, Duncan (Reformation, 2023)
Many free imperial cities played a central role in the early events of the German Reformation(s). These same cities were among the constituencies that had shaped – and been shaped by – the processes dubbed “imperial reform” (Reichsreform) by historians: discussions about and implementations of governance at the highest level in the Holy Roman Empire. This article explores the relationship between the imperial cities and imperial reform in the fifteenth century and in the early phase of the Reformation (1517–32). It argues that “imperial reform” – a historiographical construct – is best conceived as a shared discourse of peace (friden), justice (recht), and order (ordnung) associated with the new institutions created in the Empire in the crucial decades around 1500. Imperial reform remained central to the urban governments’ political agendas even as evangelical teachings spread in the years after 1517, legitimizing them and offering leverage at a time of growing tension.